Promoting data element circulation for urban digital economy development - Qiyi Han; Ying Qin (Trends in Computer Science and Information Technology - Peertechz Publications, 2023)
Data element circulation, also known as data circulation, refers to the entire process of continuously collecting, processing, storing, transmitting, and using data in economic and social activities. The rapid development of information technology has made the data elements circulation an important driving force for promoting economic growth, improving production efficiency, and fostering social innovation. However, the data elements circulation also presents a series of challenges, including data value, data security, data quality, data openness, and sharing. To fully unleash the value of data resources, improve the new foundational system, stimulate market vitality, and create a data element market with significant influence, this paper conducts a thematic study on promoting data element circulation. The significance of accelerating data element circulation, the global efforts in data element circulation, and the basic requirements for data element circulation are discussed. The paper also provides recommendations for promoting data element circulation, including policy and regulatory development, infrastructure enhancement, and continuous technological innovation. Furthermore, the paper emphasizes the importance of strengthening application scenarios, such as smart city initiatives and data center services and building a robust support system for data element circulation. The proposed strategies aim to foster high-quality development of the urban digital economy and facilitate the circulation of data elements.